0
$\begingroup$

I have the following:
Consider the basis $$B := \{\begin{pmatrix} 1 \\ 1 \\ 0 \end{pmatrix}, \begin{pmatrix} -1 \\ 1 \\ 2 \end{pmatrix}, \begin{pmatrix} 2 \\ 2 \\ 1 \end{pmatrix} \}$$ of the $\mathbb{R}^3$. Express the elements of the dual basis of $B $ in $\mathbb{(R^3)}^{*}$ as a linear combination of the canonical basis $(e^*_1,e^*_2, e^*_3)$ of $(\mathbb{R}^3)^{*}$.

Now, first I have to calculate the elements of the Dual Basis by applying $b_i^*(b_j) = \delta_{ij}$, with $b_i^*:\mathbb{R}^3 \rightarrow \mathbb{R}$ and $\delta_{ij} = 1$ for $i = j$ and $0$ else.

So for $b_1^*$ if have for example:

$$b_1^*(b_1) = \delta_{11} = 1 = 1\cdot\lambda_1 + 1\cdot\lambda_2 + 0\cdot\lambda_3$$

$$b_1^*(b_2) = \delta_{12} = 0 = -1\cdot\lambda_1 + 1\cdot\lambda_2 + 2\cdot\lambda_3$$

$$b_1^*(b_3) = \delta_{13} = 0 = 2\cdot\lambda_1 + 2\cdot\lambda_2 + 1\cdot\lambda_3$$

which translates into

$$\left(\begin{array}{ccc|c} 1 & 1 & 0 & 1 \\ -1 & 1 & 2 & 0 \\ 2 & 2 & 1 & 0 \end{array}\right)$$

and solves with $b_1^* = \begin{pmatrix} \frac{5}{2} \\-\frac{3}{2} \\ -2 \end{pmatrix}$

And if the above is correct: After solving the resulting 3 systems of linear equations I get the desired elements $(b_1^*, b_2^*, b_3^*)$ of the dual basis. The task now states to express those as a linear combination of the canonical basis $(e^*_1,e^*_2, e^*_3)$ of $(\mathbb{R}^3)^{*}$. So:

$$b_j^* = \sum_{i = 1}^3 \lambda_ie_i^* \mspace{2cm} j = 1,2,3$$

But my question now is: What are $(e^*_1,e^*_2, e^*_3)$? Are they similar to $(e_1,e_2, e_3)$ in $\mathbb{R}^3$ or do I have to calculate them separately?

If they are similar - would it really be just:

$$\begin{pmatrix} -4 \\5 \\ -2 \end{pmatrix} = \lambda_1 \begin{pmatrix} 1 \\0 \\ 0 \end{pmatrix} + \lambda_2 \begin{pmatrix} 0 \\1 \\ 0 \end{pmatrix} + \lambda_3 \begin{pmatrix} 0 \\0 \\ 1 \end{pmatrix}$$

$$\Rightarrow b_1^* = -4e_1^* + 5e_2^* - 2e_3^*$$


With the help of user7530 I now assume that they are similar:

$$e_1^*(e_1) = 1 = 1 \cdot \lambda_1 + 0 \cdot \lambda_2 + 0 \cdot \lambda_3$$ $$e_1^*(e_2) = 0 = 0 \cdot \lambda_1 + 1 \cdot \lambda_2 + 0 \cdot \lambda_3$$ $$e_1^*(e_3) = 0 = 0 \cdot \lambda_1 + 0 \cdot \lambda_2 + 1 \cdot \lambda_3$$

Which only solution is $\lambda_1 = 1$ and thus $e_1^* = \begin{pmatrix} 1 \\0 \\ 0 \end{pmatrix}$.
Same with $e_2^*,e_3^*$


Thank you very much for your help.

FunkyPeanut

$\endgroup$
  • 2
    $\begingroup$ First, you have made a calculation error somewhere, as $b_1^*(b_2) \neq 0$. Second, you can find $e_i^*$ in exactly the same way: solve for them such that $e_i^*(e_j) = \delta_{ij}$. $\endgroup$ – user7530 Apr 15 '14 at 16:04
  • $\begingroup$ Thank you! Okay - but if that is so I think I got something wrong. I thought that $b_1^{*}(b_2)$ means that $i = 1$ and $j = 2$. So we get $\delta_{12}$ which is 0 since $i \ne j$. I guess that is wrong then... Oh or do you mean the system od linear equations of you insert the solution I presented= $\endgroup$ – FunkyPeanut Apr 15 '14 at 16:08
  • $\begingroup$ You are supposed to get zero, but if I eyeball it I see that I instead get something odd. $\endgroup$ – user7530 Apr 15 '14 at 16:25
  • $\begingroup$ True. I have just corrected it $\endgroup$ – FunkyPeanut Apr 15 '14 at 16:29
2
$\begingroup$

Let the matrices $$P=[b_1\;b_2\;b_3]=\left[\begin{matrix}1&-1&2\\1&1&2\\0&2&1\end{matrix}\right]$$ and $$Q=[b_1^*\;b_2^*\;b_3^*]$$ then since $$b_i^*(b_j)=\delta_{ij}$$ we see that $$P^TQ=I_3$$ hence $$Q=\left(P^T\right)^{-1}=\frac12\left[\begin{matrix}-3&-1&2\\5&1&-2\\-4&0&2\end{matrix}\right]$$

$\endgroup$
  • $\begingroup$ Wow this looks amazing. But I don't quite see how you achieved that. Why do we see that $P^T Q = I_3$? $\endgroup$ – FunkyPeanut Apr 15 '14 at 16:32
  • $\begingroup$ In your answer you wrote $$\left(\begin{array}{ccc|c} 1 & 1 & 0 & 1 \\ -1 & 1 & 2 & 0 \\ 2 & 2 & 1 & 0 \end{array}\right)$$ hence $$P^T\left(\begin{array}\\ \lambda_1 \\ \lambda_2 \\ \lambda_3\end{array}\right)=\left(\begin{array}\\ 1 \\ 0 \\ 0\end{array}\right)$$ so do the same thing for the other vectors and you find the equality. $\endgroup$ – user63181 Apr 15 '14 at 16:45
  • $\begingroup$ I just saw that. Dude you are so awesome I can't describe... Seeing things like that is one reason why I study this! Thank you!! $\endgroup$ – FunkyPeanut Apr 15 '14 at 16:49
  • $\begingroup$ You're welcome:-) $\endgroup$ – user63181 Apr 15 '14 at 16:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.